2011
DOI: 10.1016/j.bpj.2011.03.048
|View full text |Cite
|
Sign up to set email alerts
|

An Ion Switch Regulates Fusion of Charged Membranes

Abstract: Here we identify the recruitment of solvent ions to lipid membranes as the dominant regulator of lipid phase behavior. Our data demonstrate that binding of counterions to charged lipids promotes the formation of lamellar membranes, whereas their absence can induce fusion. The mechanism applies to anionic and cationic liposomes, as well as the recently introduced amphoteric liposomes. In the latter, an additional pH-dependent lipid salt formation between anionic and cationic lipids must occur, as indicated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…48 An explanation might be that the electrostatic interaction in basic conditions might be reduced due to the screening of the positive charge of DOTAP by HPO 4 2À since this divalent counter ion (the dominant anionic ion in PBS) might effectively bind to DOTAP. 53,54 Moreover, these counter ion might also generate an entropic repulsion when vesicles approach the gold surface as reported by Zhu et al 55 These effects might weaken the electrostatic adhesion force of the lipid to the surface.…”
Section: B Influence Of the Ph On The Bilayer Formationmentioning
confidence: 88%
“…48 An explanation might be that the electrostatic interaction in basic conditions might be reduced due to the screening of the positive charge of DOTAP by HPO 4 2À since this divalent counter ion (the dominant anionic ion in PBS) might effectively bind to DOTAP. 53,54 Moreover, these counter ion might also generate an entropic repulsion when vesicles approach the gold surface as reported by Zhu et al 55 These effects might weaken the electrostatic adhesion force of the lipid to the surface.…”
Section: B Influence Of the Ph On The Bilayer Formationmentioning
confidence: 88%
“…Third, ether linkages often used to anchor polyethylene glycol (PEG) or pH responsive headgroups are not used. Finally, the amphoteric nature enables a transition of charge from cationic to net neutral to anionic or vice versa depending on the microenvironment [ 24 , 26 ]. For example, during transient acidic ethanolic conditions used during formulation, there is an overall positive charge to the mixture enabling the efficient encapsulation of the negatively charged PNT100.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the unique mixture of lipids (that lack ether linkages or PEG) and particle size of the amphoteric liposomes contributes to the therapeutic activity of PNT2258 in several ways. These include imparting stability [ 24 , 26 ], surface characteristics which prolong circulation times in blood, and permit metabolic breakdown to enable repeated dosing. Toxicology findings in preclinical studies with PNT2258 showed dose-dependent toxicities that were reversible, and attributable to high doses of lipid (>300 mg/kg) rather than PNT100 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their anionic state averts the aggregation of serum components thereby promoting serum stability and reducing toxicities. Their cationic state mediates efficient encapsulation of oligonucleotides during production and fusion with endosomes, thereby enabling endosomal escape within the cells [97].…”
Section: Pnt2258mentioning
confidence: 99%